Naturalistic Ecolinguistics Learning Model in the Framework of Green Ecology: Development Urgencies (Model Pembelajaran Ekolinguistik Naturalistik dalam Rangka Green Ecology: Urgensi Pengembangan) - R. Kunjana Rahardi (Jurnal Gramatika, 2023)
Extreme weather phenomena have become more frequent, and the natural environment has suffered due to rampant deforestation, logging, and unchecked forest clearance. These issues have captured global attention. The primary objective of this research is to underscore the necessity for the formulation of a naturalistic ecolinguistic learning paradigm. This study is rooted in ecolinguistic theory, specifically focusing on naturalistic ecolinguistics and the creation of educational materials for higher education institutions. The research methodology employed in this investigation is characterized as descriptive quantitative research, incorporating basic statistical techniques. The target population comprises students enrolled in the language education master's program, particularly those who have participated in courses on ecolinguistics, particularly the naturalistic branch. Through purposive selection, a sample size of 30 respondents, consisting of current students and alumni from Sanata Dharma University's Master of Language Education program, who have undergone training in naturalistic ecolinguistics, was determined. Participants were presented with a series of 20 statements, rated on a Likert scale, soliciting their agreement or disagreement. The findings reveal an overwhelming consensus among respondents, with approximately 90% expressing support for the development of a naturalistic ecolinguistic learning model. The prevailing sentiment is that this initiative is of utmost importance, aligning with the university's commitment to the green ecology program